e-LKPD Berbasis Project Based Learning Berpendekatan STEM Materi Fluida Dinamis untuk Meningkatkan Literasi Sains - Ana Maulida; Dwi Yulianti (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2025)
This study aims to describe e-LKPD based on PjBL-STEM in improving students' scientific literacy, determine the feasibility and readability of e-LKPD, and the development of students' scientific literacy after its implementation. The study used the R&D method with the ADDIE model and a quasi-experimental nonequivalent control group design approach. The research subjects consisted of grade XI students of MAN 1 Kab. Semarang. Data were collected through observation, interviews, and written tests. The e-LKPD with the STEM approach was compiled according to the PjBL syntax and contained indicators of scientific literacy. The validation results showed a very feasible category, while readability was in the very good category. The increase in scientific literacy of students in the experimental class was higher than in the control class. The conclusion shows that e-LKPD based on PjBL-STEM is effective in improving students' scientific literacy.